Association of HLA Class I Antigens with Diffuse Panbronchiolitis in Korean Patients - PARK, MYOUNG HEE; KIM, YOUNG WHAN; YOON, HO IL; YOO, CHUL-GYU; HAN, SUNG KOO; SHIM, YOUNG-SOO; KIM, WON DONG (American journal of respiratory and critical care medicine, 1999)
Diffuse panbronchiolitis (DPB) is a chronic obstructive pulmonary disease of unknown etiology. Observations of significantly increased frequency of human leukocyte antigen (HLA)-B54 in Japanese patients and occurrence of familial cases suggest possible genetic predisposition to the disease susceptibility. To evaluate the possible association of HLA with the disease in Koreans, we have analyzed 30 patients for HLA class I (A, B, C) and class II (DR) antigens by the serologic and DNA typing methods, respectively. The most significant change in the patients compared to the control subjects was increased frequency of HLA-A11 (53.3% versus 17.5%, corrected p [pc] = 1.2 x 10(-)4, odds ratio [OR] = 5.4). In addition, B55 showed significant positive association (16.7% versus 3.5%, pc = 0.05, OR = 5.5), and B62 and Cw4 showed rather weak association with the disease. Certain A11-associated haplotypes showed much stronger positive association with the disease, compared to A11 antigen itself. Observations of a strong association of HLA-A11 in Koreans and B54 in Japanese with DPB suggest that the candidate gene(s) responsible for the disease susceptibility is located within the HLA class I region, most probably between HLA-A and HLA-B loci.